Association of healthcare worker behaviors with coronavirus disease 2019 (COVID-19) risk during four pandemic periods and characteristics associated with high-risk behaviors. Issue 1 (17th January 2023) - Egbert, Emily R.; Xiao, Shaoming; Prochaska, Erica; Ali, S. Omar; Colantuoni, Elizabeth; Gadala, Avi; Koontz, Danielle; Zhong, Diana; Schumacher, Christina M.; Sick-Samuels, Anna C.; Debes, Amanda K.; Milstone, Aaron M.
Abstract: In a large healthcare worker cohort, we quantified the association between behaviors and risk of coronavirus disease 2019 (COVID-19) during different pandemic phases, adjusting for prior infection and vaccination. Individual characteristics, including personal concerns, were associated with these behaviors. Public health messaging should target high-risk populations and behaviors as the pandemic evolves.